Eighth Review of the Fund's Data Standard Initiatives. (Policy Papers; Policy Paper ;, 2012)
This paper reports on developments in the Data Standards Initiatives since the Seventh Review of the Fund's Data Standards Initiatives (December 2008), and presents proposals for further enhancing the SDDS, and for data categories for the new higher tier of the data standards, the SDDS Plus. The SDDS Plus is primarily intended for subscribers to the SDDS with systemically important financial sectors while contributing to address further the data gaps revealed in the global financial crisis. This new tier is designed to enhance and supplement the Fund's Data Standards Initiatives and not to replace the SDDS.